Research on a new network covert channel model in blockchain environment - Yanfeng LI; Liping DING; Jingzheng WU; Qiang CUI; Xuehua LIU; Bei GUAN (Tongxin xuebao)
Blockchain is a decentralized architecture emerging with cryptocurrencies,which is credible and robust.A network covert channel model in blockchain environment was proposed for the first time,which was anti-interference,anti-tamper modification,multi-line communication,receiver anonymity and line independence.The shortcomings of network covert channel in existing network environment could be tackled by the new type of network covert channel,such as characteristic defect.etc.Firstly,A network covert channel model in blockchain environment was presented by formal method,its anti-interference and anti-tamper modification was proved.Then,a blockchain network covert channel scenario using service operation interval time was presented.Finally,the undetectability,robustness and rate of the blockchain network covert channel evaluation vectors was proposed.A theoretical foundation was laid for the practicality of the new type of network covert channel in blockchain.